Plazmoniczne właściwości anizotropowych, ultracienkich warstw złota oraz wynikający z nich dichroiczny efekt Ramana, ukierunkowane na rozwój powierzchniowo wzmocnionej spektroskopii Ramana (SERS) - Ephraim, Mathew (My University, 2026)
Niniejsza rozprawa koncentruje się na badaniu właściwości plazmonicznych ultracienkich warstw Au osadzonych na pofałdowanych matrycach Al₂O₃, w celu ich wykorzystania w spektroskopii ramanowskiej wzmocnionej powierzchniowo. Te podłoża plazmoniczne wytworzono poprzez osadzanie ultracienkich warstw Au na pofałdowanych matrycach Al₂O₃. Zaobserwowano wzbudzenie zlokalizowanych modów plazmonów powierzchniowych (LSPP) zhybrydyzowanych jako kolektywne mody plazmonowe. Pomiary spolaryzowanego pola magnetycznego (TAS) wykonane na tych próbkach porównano z pomiarami w stanie stacjonarnym. Natomiast propagujące się hybrydowe mody plazmonów powierzchniowych (SPP) wzbudzono na połączonych perkolowanych warstwach Au (wykazujących cechy metalu Drudego). Ponadto, w pomiarach spolaryzowanego pola magnetycznego (SERS) zaobserwowano wzmocnioną, dichroiczną odpowiedź analitów tiofenolowych w SERS. 1, Przeanalizowano i zinterpretowano dichroizm SERS pików drgań Ramana analitu sondy o różnych częstotliwościach przesunięcia Stokesa, aby zweryfikować mechanizm elektromagnetyczne SERS. 2, Przeanalizowano i zinterpretowano dichroizm SERS modów drgań Ramana analitu sondy o różnych tensorach polaryzowalności. This thesis focuses on the study of plasmonic properties of ultrathin Au films deposited on corrugated Al2O3 templates, for utilizing it as an application for surface enhanced Raman spectroscopy substrate, and studying its Raman scattering amplification processes. These plasmonic substrates were fabricated by depositing ultrathin Au films onto corrugated Al2O3 templates. Excitation of localized surface plasmon polariton (LSPP) modes hybridized as collective plasmon modes was observed due to the strong coupling between the MNPs in these arrays. Polarized-TAS measurements performed on these samples were compared with the steady state measurements. In contrast, propagating hybrid surface plasmon polariton (SPP) modes were excited on connected percolated Au films (exhibiting Drude metal characteristics). The experimental observations were corroborated with EM simulations. Further, enhanced, dichroic SERS response of thio-phenol analytes was observed in Polarized SERS measurements. 1, The SERS dichroism of probe analyte’s Raman vibration peaks of different Stokes shifted frequency was analyzed and interpreted to verify the EM nearfield mechanism of SERS enhancement. and 2, The SERS dichroism of probe analyte’s Raman vibration modes of different polarizability tensor was analyzed and interpreted to the study surface selection rules on these samples and their relative Raman peak intensity enhancements. This work provides an understanding for the design of plasmonic SERS substrates based on these ultrathin Au metal nanostructures.
Plasmonic properties of anisotropic, ultra-thin Au films and its resulting dichroic Raman effect towards the development of surface enhanced Raman spectroscopy.
Wydział Fizyki
Keywords: Polaritony plazmonowe w ultracienkich warstwach; warstwy perkolowane i nieperkolowane; mechanizm bliskiego pola elektromagnetycznego; podpromienisty i nadpromienisty SERS; spolaryzowany SERS.; Plasmon polaritons in ultrathin film plasmonics; percolated and non-percolated films; EM near-field mechanism; Sub and super radiant SERS; Polarized SERS.